Listen to my trumpet! - Willems, Mo. (2012)
When Piggie plays her new trumpet for Gerald, the elephant decides he must be honest in his response.
Keywords: Swine -- Juvenile fiction; Elephants -- Juvenile fiction; Trumpet -- Juvenile fiction; Friendship -- Juvenile fiction; Fiction